Igreja Evangélica Livre do Brasil 1936-2017: entre a pátria alemã e a nação brasileira. - Vieira, Raimundo Nonato (2018)
This dissertation aims to make a historical description of the Evangelical Free Church of Brazil. To this end, it seeks the relation of the origin of this denomination in Europe with the arising of independent religious movements from the Protestant Reformation of the fourteenth century. After locating the group in the Free Churches worldwide movement, this research seeks to describe the emergence of its historical embryo since German and Swiss immigrants coming to São Paulo, from Free Evangelical Churches in Europe, and how they try to transplant their original religious identity to their new homeland. In the meantime, the first German missionaries come to Brazil, not to support the implementation of Churches for immigrants, but with the firm intention of starting new Churches for Brazilians, among Brazilians. For this, they choose the interior of Paraná, where they started orphanages, day care centers and, later, other organs to strengthen the achievement of this missionary initiative. But this distinct choice of the group of immigrants from Sao Paulo will bring tension between the two groups. Finally, this research describes the Free Evangelical Church in recent years, after taking over the responsibility for this religious enterprise and seek to understand how a structure with departments and institutions is created to give plausibility to the process of institutionalization that was in progress. In order to understand the whole historical plot from a non-theological perspective of the events and their sequence, the theory of Peter L. Berger and Thomas Luckmann was used in “The Social Construction of Reality”.